2019
DOI: 10.1111/pace.13661
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cutoff value of bipolar low‐voltage in electroanatomic voltage mapping during atrial fibrillation rhythm

Abstract: Background Electroanatomic voltage mapping (EAVM) of the left atrium (LA) with multielectrodes is usually acquired during sinus rhythm (SR), and the feasibility of EAVM during atrial fibrillation (AF) rhythm is unclear. Methods We performed EAVM of LA during both SR and AF rhythm in 44 patients undergoing catheter ablation for AF and validated the optimal cutoff value of low‐voltage area (LVA) during AF rhythm for detecting LVA defined as bipolar voltages ≤0.5 mV during SR. Results In each session, mean 829 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The clinical outcomes were compared with those in the historical controls who underwent catheter ablation for persistent AF with minimum additional ablation only for induced and sustained AF (21.9%). The details of ablation procedure for these historical controls were previously reported as the minimum substrate ablation 8 . Statistical analyses were performed using JMP 10 (SAS Institute Inc, Cary, NC) software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical outcomes were compared with those in the historical controls who underwent catheter ablation for persistent AF with minimum additional ablation only for induced and sustained AF (21.9%). The details of ablation procedure for these historical controls were previously reported as the minimum substrate ablation 8 . Statistical analyses were performed using JMP 10 (SAS Institute Inc, Cary, NC) software.…”
Section: Methodsmentioning
confidence: 99%
“…The details of ablation procedure for these historical controls were previously reported as the minimum substrate ablation. 8 Statistical analyses were performed using JMP 10 (SAS Institute Inc, Cary, NC) software.…”
Section: Definitions Outcome Measures and Statistical Analysismentioning
confidence: 99%
“…Femoral venous access was used for double trans‐septal puncture, followed by heparinization to ACT >350 s. The baseline charge density map (pre‐PVI) was acquired for 30 s during AF with AcQMap, followed by a high density (>3000 points) contact map of the left atrium (LA) during AF using a multipolar catheter, either Advisor FL SE or Advisor HD Grid SE (Abbott Medical). A threshold of 0.2 mV (in AF) was used to define LVA as this has been shown to correlate with the conventional definition of 0.5 mV in sinus rhythm and with the presence of a scar on MRI 14,20 . Pulmonary vein isolation (PVI) was then performed either by de novo wide area circumferential ablation ( n = 6), or for redo procedures ( n = 10) at regions of vein reconnection with contact force guidance (TactiCath SE; Abbott Medical).…”
Section: Methodsmentioning
confidence: 99%
“…Catheter ablation is a first line therapy for patients with persistent AF 3 . Substrate ablation strategies guided by a voltage map derived from the amplitude of intracardiac electrograms define areas based on a cut-off value (frequently < 0.5 mV during sinus rhythm) as pathological tissue and target them for ablation [4][5][6] . Several clinical studies have shown a correlation of fibrosis identified through late gadolinium enhancement magnetic resonance imaging (LGE-MRI) with reduced local signal amplitude ("voltage") in atrial electrograms 7,8 .…”
Section: Introductionmentioning
confidence: 99%